Assessment of Basotho women's perceptions of the health risks associated with skin-lightening in Lesotho using the Health Belief Model - Makutoane, Ntseke (Department of Public Health and Family Medicine, 2024)
The practice of skin lightening has existed for centuries and is still prevalent today despite globally coordinated legal efforts to ban harmful skin-lightening agents in cosmetic items. Exposure to toxic compounds such as mercury, hydroquinone, and corticosteroids commonly found in skin-lightening products (SLPs) is associated with several adverse health risks such as adrenal disorders, hypertension, neurological problems, skin cancers, and skin atrophy. Despite the documented health risks, the practice of using highly hazardous products for skinlightening is a global public health concern that is receiving little attention. These products are commonly and freely displayed for sale on the streets and are available over the counter in many countries, including Lesotho. The SLPs were primarily intended as medical treatments for hyperpigmentation and other skin problems, but they have since gained commercial use for skin lightening. Policy interventions such as public health campaigns, research, and community-based education necessitate execution to curb skin-lightening demand and practices. Research evidence is therefore needed to inform these activities. There are currently no published studies in Lesotho highlighting why Basotho women use SLPsto inform risk reduction interventions. Hence, the need for this research. The research protocol (part A) articulates the justification and rationale of the study and describes the methodology utilized for recruitment, data collection, and analysis. It also includes a review of the literature on the history of skin lighteners, skin-lightening practice in Sub-Saharan Africa (SSA), women's motivation for skin lightening, current interventions to prohibit skin-lightening practices, and the health risks of mercury, hydroquinone, and corticosteroids in skin-lightening products. The protocol discusses ethical considerations to ensure the confidentiality of participants. The study was approved by the University of Cape Town's Health Sciences Faculty Research Ethics Committee and the Ministry of Health Ethics Clearance Committee in Lesotho. The Lesotho COVID-19 protocols were considered during the study. The journal-ready article (part B) presents the study findings on the Basotho women's attitudes of the use of SLPs, perceptions of the perceived benefits of skin-lightening, knowledge of skin-lightening health risks, and interventions that have been effective in preventing the usage and importation of SLPs in low- and middle-income countries. The study vi found that women have varying perceptions of the health risks and motivations for using SLPs. Sociodemographic factors such as age, marital status, skin tone classification, and education level had no significant role in women's decision to practice skin-lightening. Fifty-two percent of participating women, from all skin tone categories, claimed to have used SLPs. The most common motivations for using SLPs included a desire to acquire a lighter skin complexion, to remove facial blemishes, and to beautify themselves. Lack of regulations on SLPs, skin tone discrimination, and fixing the damage from overuse of SLPs were identified as perceived barriers in discouraging women from using SLPs. Regardless of whether participating women lightened their skin, about two-thirds rejected the notion that lighter skin is more attractive and increases a woman's chances of getting married. According to the study's key informants (government officials and a senior lecturer at the National University of Lesotho), the lack of national legislation on SLPs has mainly been attributed to the Lesotho Parliament's failure to domesticate the Minamata Convention on Mercury. The results of the study are intended to serve as a benchmark for future research on skin-lightening practices in Lesotho. Limitations of the study included the results' generalizability since non-randomised convenience sampling was used. Awareness-raising campaigns and the availability of legislation regulating hazardous chemicals in SLPs are needed interventions to control the usage of SLPs. The appendices (part C) provide the informed consent for women, informed consent for key informants, questionnaire for women, interview guide for key informants, ethical clearance from the University of Cape Town's Health Sciences Faculty Research Ethics Committee, ethical clearance from the Ministry of Health Ethics Clearance Committee in Lesotho, a codebook, and publishing instructions for the Environmental Health Journal.